O feminino e a natureza CATHERINE EARNSHAW em WUTHERING HEIGHTS DE EMILE BRONTË. - Castro, Elessandra Barbosa de Araújo (Universidade Federal do Tocantins, 2022)
Emily Brontë‟s Wuthering Heights, 1847, is considered a classic in English Literature. This work, focusing on the connection of nature and the female, has, as its initial objective, to analyze the connection of the concept of nature and the female protagonist, Catherine Earnshaw. Our first step was an attempt to define, through theoretical concepts, Romanticism; and show how elements of the natural world are related to the movement. Next, we comment on the Victorian ideals for women, applying these concepts to the life of the Brontë sisters. Finally, we comment the novel, with emphasis on the Catherine as a female character: a savage girl, her transgressions of the norm and, specially, he relation to nature and the facts that interconnect her to the other characters. To help us in our analysis we have consulted books on Romanticism and Nature, e our main sources were: The Cambridge Introduction to Literature and the Environment by Timonthy Clark and Aspectos da natureza no Romantismo: um recorte crítico by Alexandre de Melo Andrade; among others such as Aidan Day e Willian Wordsworth.